Incoherent microwave-induced resistive states of small Josephson junctions - Koval, Y.; Fistul, M.V.; Ustinov, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We report an experimental and theoretical study of low-voltage resistive states that are observed in small tunnel Josephson junctions under microwave radiation. The studied features emerge from Shapiro steps on the current- voltage characteristics and appear when both thermal fluctuations and high frequency dissipation are strong. In the absence of microwave radiation Josephson junctions display under these conditions a phase diffusion supercurrent branch characterized by a finite small resistance and hysteretic switching to high voltage range. As the microwave radiation is applied, we experimentally observe three different types of resistive states in the currentvoltage characteristics. First, the phase diffusion branch steadily evolves and its maximum reached voltage Vm increases with the microwave power. Another interesting observed feature is a zero-crossing resistive state characterized by a negative resistance. Finally, we find that a low-voltage resistive state can split in numerous hysteretic fine branches resembling incoherent Shapiro-like steps. The appearance of a particular resistive state depends on an interrelation between the Josephson energy EJ, energy of thermal fluctuations kBT, and the frequency of microwave radiation ω. Our theoretical analysis based on an incoherent multi-photon absorption of a junction biased in the Josephson phase diffusion regime, is in a good accord with experimental observations.